2019
DOI: 10.1186/s43088-019-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic multi-criteria decision-making: an overview to methods and applications

Abstract: Background: The alternatives selection problem with multi-criteria in stochastic form variables is called as stochastic multi-criteria decision-making. The stochasticity of the criteria is considered using stochastic dominance, prospect theory, and regret theory.Main text: In this paper, a total 61 papers are reviewed and analyzed based on method(s) used in stochastic multicriteria decision-making problem, method used in stochasticity, specific objective, application area, and so on classification. All papers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…This fuzzy set concept reflects uncertainty more robustly and accurately (Mendel et al 2006 ). This fuzzy set extension has been applied to many multi-criteria decision-making (MCDM) problems due to ease of calculation, the necessity of reflecting the uncertain environment in decision-making, and difficulties in obtaining precise data (Celik et al 2019 ). Celik et al’s ( 2015 ) study can be seen in a detailed literature review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fuzzy set concept reflects uncertainty more robustly and accurately (Mendel et al 2006 ). This fuzzy set extension has been applied to many multi-criteria decision-making (MCDM) problems due to ease of calculation, the necessity of reflecting the uncertain environment in decision-making, and difficulties in obtaining precise data (Celik et al 2019 ). Celik et al’s ( 2015 ) study can be seen in a detailed literature review.…”
Section: Methodsmentioning
confidence: 99%
“…IT2F-BWM was initially proposed by Wu et al ( 2019 ) and applied to the green supplement selection problem. In supplier selection problems, Celik et al ( 2019 ) found the most suitable supplier IT2F-BWM and TODIM. Hoseini et al ( 2021 ) used BWM in combination with TOPSIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of its ability to accommodate high levels of ambiguity and uncertainty, SMCDM has gained considerable popularity in addressing MCDM problems in a variety of scenarios. In a detailed review, Celik et al ( 2019 ) found that more than a quarter of the applications of SMCDM were to finance problems. These applications focus on specific issues such as credit scoring, investment project choices, enterprise selection, pension fund selection, bank investment evaluation, and even luxury car selection.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…In order to assess this, a probabilistic approach can be taken, using stochastic (Monte-Carlo) simulation to run a predetermined number of iterations of the MCE workflow, subjecting its criteria to the fluctuations derived from the RMSE. Stochastic processes are sometimes used in flood risk modelling and MCE independently (Celik et al, 2019), but there is no literature which combines stochastic modelling and MCE analysis when evaluating flood risk. This study therefore aims to fill in the existing void in the literature, and hopefully encourage other authors to adopt similar techniques in their own research.…”
Section: Introductionmentioning
confidence: 99%